Self-Proving Affidavits and Formalism in Wills Adjudication - Bruce H. Mann (Washington University Law Quarterly, 1985)
This Article makes a small effort toward an alternate explanation of formalism in wills adjudication. It is prompted by an odd and rather perverse line of cases from Texas. The cases are interesting not for their content or logic, but because they provide a rare opportunity to observe the creation, elaboration, and entrenchment of a new formality for the proper execution of wills—one that treats the use and misuse of self-proving affidavits. That the cases are from Texas is incidental. Their value lies in their suggestion that formalism in wills adjudication may persist because of the structure of the probate process and its historical position within the legal system. As an explanation of formalism, this Article can only be partial, but it may suggest a useful way of looking at an old and intractable problem.
Keywords: Wills; Affidavits